Effectiveness of a Community-Based Educational Intervention on Dental Caries Preventive Behavior Among the Kolok Community in Bengkala Village, Bali - Yudha Rahina; Ni Putu Idaryati; I Nyoman Panji Triadnya Palgunadi; Komang Riska Cahya Ningrum; Dentino Asmara Putra (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: The Kolok (deaf–mute) community in Bengkala Village has limited access to health information due to the use of a local sign language restricted to the community. Consequently, poor knowledge and oral hygiene, as well as many complaints of toothache. This study aimed to evaluate the effectiveness of oral health education on caries-preventive behaviors among the Kolok community. Materials and Methods: A pre-experimental one-group pretest–posttest design was conducted involving 34 Kolok individuals aged 20–60 years, selected randomly. The intervention comprised face-to-face oral health education assisted by a local interpreter and the use of a toothbrushing calendar. Changes in oral health knowledge and preventive behaviors were assessed over two months. Knowledge was measured using questionnaires, while behaviors were assessed using questionnaires and the Oral Hygiene Index Simplified (OHI-S). Data were analyzed using paired sample t-tests, Wilcoxon signed-rank tests, independent sample t-tests, and Mann–Whitney U tests. Results and Discussion: The results indicated significant differences in knowledge and caries preventive behaviors between the intervention and control groups after the intervention (p < 0.05). However, significant improvements were observed in the control group, whereas no significant changes were found in the intervention group. In contrast, oral hygiene status significantly improved in the intervention group. Conclusion: Face-to-face oral health education assisted by a local interpreter was not effective in improving oral health knowledge and caries-preventive behaviors among the Kolok community. Nevertheless, the toothbrushing calendar demonstrated effectiveness in improving oral hygiene to prevent caries.